2010
DOI: 10.1088/0004-637x/711/1/517
|View full text |Cite
|
Sign up to set email alerts
|

Long-Duration Radio Transients Lacking Optical Counterparts Are Possibly Galactic Neutron Stars

Abstract: Recently, a new class of radio transients in the 5 GHz band and with durations of the order of hours to days, lacking any visible-light counterparts, was detected by Bower and collaborators. We present new deep near-infrared (IR) observations of the field containing these transients, and find no counterparts down to a limiting magnitude of K = 20.4 mag. We argue that the bright (>1 Jy) radio transients recently reported by Kida et al. are consistent with being additional examples of the Bower et al. transients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 115 publications
(208 reference statements)
2
58
0
Order By: Relevance
“…Among these typical radio SNe are the most abundant. Transient search over 1/17 of the sky with F lim = 6 mJy at 1.4GHz (Levinson et al 2002;Gal-Yam et al 2006;Ofek et al 2010) finds one radio SN. This rate translates to 10 3 − 10 4 SNe in a whole sky F lim = 0.1 mJy survey.…”
Section: Identification and Contaminationmentioning
confidence: 99%
“…Among these typical radio SNe are the most abundant. Transient search over 1/17 of the sky with F lim = 6 mJy at 1.4GHz (Levinson et al 2002;Gal-Yam et al 2006;Ofek et al 2010) finds one radio SN. This rate translates to 10 3 − 10 4 SNe in a whole sky F lim = 0.1 mJy survey.…”
Section: Identification and Contaminationmentioning
confidence: 99%
“…However, in the drift-scanning observations of the Nasu sky survey, the area and time were not independent, which may have introduced anomalies in the discovery rates. In Section 5, we revise the discovery rate in terms of the definition in Ofek et al (2010) and the reliability evaluation results presented in Section 4. …”
Section: Previous Analysismentioning
confidence: 99%
“…In terms of duration time, discovery rate, and lack of clear counterparts, these events were similar to Bower's transients. This similarity inspired Ofek et al (2010) to argue the origins of the transients. They concluded that the likely origins were old Galactic neutron stars.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the RRATS have much shorter durations than WJN transients. In another example, 10 radio transient signals have been discovered in archival data from the VLA spanning 22 yr with a typical 7-day epoch separation (Bower et al 2007;Ofek et al 2009). Reanalysis has revealed that six signals were derived from artifacts or side lobes of bright sources (Frail et al 2012).…”
Section: Introductionmentioning
confidence: 99%